The Effect Of Short Drink Cans And Steel Fibers On The Flexural Performance Of Concrete Beams - Shanmugan Nagappan (2023)
The amount of drink cans nowadays keeps increasing as rubbishnear the rural and urban area as waste product without any effective solution to dispose it.